38.9k views
2 votes
Make t the subject of the formula 2(d – t) = 4t + 7

User Buena
by
4.8k points

2 Answers

4 votes

Explanation:

2(d-t)=4t +7

open the bracket

2d - 2t =4t +7

collect like terms

2d-7=4t +2t

2d-7=6t

divide both sides by 6

2d-t/6=6t/6

T=2d-t/6

User Mawcel
by
4.7k points
2 votes

Answer:

t = (2d-7)/6

Explanation:

2(d – t) = 4t + 7

Distribute

2d-2t=4t+7

Add 2t to each side

2d-2t+2t=4t+2t+7

2d = 6t+7

Subtract 7 from each side

2d-7 = 6t

Divide by 6

(2d-7)/6 = t

User Enguerranws
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.